Factors Affecting the Likelihood of Undergoing Transoral Robotic Surgery for Head and Neck Cancer. (2nd September 2014) - Squires, Lane D.; Steele, Toby O.; Biron, Vincent L.; Luu, Quang K.; Farwell, D. Gregory; Bewley, Arnaud F.
Abstract : Objectives: Evaluate whether patient demographics and hospital characteristics are associated with a patient's likelihood of undergoing transoral robotic surgery (TORS) for head and neck cancer. Methods: A cross‐sectional analysis of 13, 193 patients who were admitted to US hospitals in 2009 and 2011 with a primary diagnosis of head and neck cancer was performed using data from the Nationwide Inpatient Sample. A multinomial logistic regression model was used to calculate the likelihood of undergoing TORS based on age, sex, race, household income quartile, insurance status, hospital size, hospital region, and hospital teaching status. Results: A total of 181 patients underwent TORS for head and neck cancer in the years 2009 and 2011. With regard to demographic factors, Hispanic patients and those within the lowest 2 income quartiles were significantly less likely to undergo TORS when compared with white patients and those within the highest income quartile (odds ratio [ORs] 0.27 confidence interval [CI; 0.09‐0.80], 0.48 CI [0.29‐0.80], 0.54 CI [0.34‐0.87]). With regard to hospital characteristics, patients treated at hospitals in the northeast and south and those treated at nonteaching hospitals were significantly less likely to undergo TORS than those treated at hospitals in the west and those treated at teaching hospitals (ORs 0.48 CI [0.31‐0.73], 0.43 CI [0.28‐0.64], 0.27 [0.16‐0.44]). There were no significant differences found between patients of different age groups or patients treated at different sized hospitals. Conclusions: Racial, socioeconomic, and regional disparities exist in the availability of TORS to head and neck cancer patients.